Social factors As determinants of teenage pregnancy proneness among public secondary school students in Ibadan, Oyo State (2021)
In Nigeria, teenage pregnancy among secondary school students is becoming rampant. In this study, the authors investigated the effect of social factors' (parental support, parenting style, peer influence, social media usage and sexuality education) associated with proneness to teenage pregnancy among secondary school students in Ibadan, Oyo State, Nigeria. The study adopted a non-experimental research design of survey type. Population comprised all SSS II students in public secondary schools in Ibadan Metropolis out of which 1200 students (600 Boys and 600 girls) were sampled through multistage sampling procedure. Two instruments used for this study were Social Factors Questionnaire (SFQ) and Perception to Teenage Pregnancy Questionnaire (PTPQ). The findings revealed that social media usage (β = 0.09, t = 2.32), parenting style (β =0.07, t = 2.14) and sexuality education (β = 0.11, t = 3.90) contributed significantly to the prediction of male proneness to pregnancy. Also, social media usage (β = 0.10, t = 2.27) contributed significantly to the prediction of female proneness to pregnancy. Parental support (β = 0.05, t = -1.24), parenting style (β = -0.07, t = -1.80), peer influence (β = 0.07, t = 1.62) and sexuality education (β = 0.06, f= 1.68) did not contribute significantly to female proneness to teenage pregnancy. The authors concluded that parents and tall: educational stakeholders should join hands to guide youth against the. menace of teenage pregnancy.